The Emotional Quotient Competence and Tri Hita Karana Culture Moderating the Influence of Task Complexity towards the Auditor Performance - Juliantara I Komang; Edy Sujana; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2023)
Challenges in auditor performance with increasing task complexity result in a decrease in the quality of auditor performance. The research aimed at proofing the emotional quotient competence and Tri Hita Karana culture in moderating the influence of task complexity on auditor performance. The population of this research was the auditor at the Public Accountant Office in Bali. The sample was chosen using a purposive sampling technique. The data analysis used SEM-PLS (Structural Equation Modeling-Partial Least Square) assisted by the software SmartPLS Version 3. The result of the research shows that the complexity of the task influences negatively significant towards the auditor's performance. The task complexity influences dominantly towards the auditor's performance. The emotional quotient influences positively significant towards the auditor's performance. The culture of Tri Hita Karana influences positively significant towards the auditor performance. The emotional quotient significantly moderates the complex influences of tasks on the auditor's performance. More specifically, the emotional quotient weakens the negative influence of task complexity on auditor performance. The culture of Tri Hita Karana significantly moderates the influence of task complexity on auditor performance. Specifically, the culture of Tri Hita Karana weakens the negative influence of task complexity on auditor performance. The implication of this study is the importance of improving emotional intelligence skills and the implementation of Tri Hita Karana culture as supporting factors to improve auditor performance in facing task complexity.